2020
DOI: 10.1109/access.2020.2971225
|View full text |Cite
|
Sign up to set email alerts
|

Medical Image Classification Using a Light-Weighted Hybrid Neural Network Based on PCANet and DenseNet

Abstract: Medical image classification plays an important role in disease diagnosis since it can provide important reference information for doctors. The supervised convolutional neural networks (CNNs) such as DenseNet provide the versatile and effective method for medical image classification tasks, but they require large amounts of data with labels and involve complex and time-consuming training process. The unsupervised CNNs such as principal component analysis network (PCANet) need no labels for training but cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…DenseNet-161 has demonstrated a superb performance for ILSVRC ImageNet classification task [ 43 ]. Moreover, DenseNet-161 has shown a great success in several histopathological image analysis pipelines [ 10 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. In order to supply the patch-wise feature extractor network with image patches, we extract a number of patches k based on the following equation [ 7 ]: where W and H are width and height dimensions of the input image, respectively.…”
Section: Proposed 3e-net Modelmentioning
confidence: 99%
“…DenseNet-161 has demonstrated a superb performance for ILSVRC ImageNet classification task [ 43 ]. Moreover, DenseNet-161 has shown a great success in several histopathological image analysis pipelines [ 10 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. In order to supply the patch-wise feature extractor network with image patches, we extract a number of patches k based on the following equation [ 7 ]: where W and H are width and height dimensions of the input image, respectively.…”
Section: Proposed 3e-net Modelmentioning
confidence: 99%
“…4(b) ] adds separable convolution to VGG16 as well as the layer-jumping connection structure of DenseNet. DenseNet 27 can connect each layer in the network with the previous layer to enhance feature utilization, reorganize all feature maps at the end to achieve maximum utilization of resources and compression of calculations, and increase the speed as much as possible while improving model classification capabilities.…”
Section: Methodsmentioning
confidence: 99%
“…DenseNet201 present state-of-art CNNs is notable for its astonishing performance in benchmark tasks such as CIFAR-100 and ImageNet, which require competitive object recognition. Recent studies have shown that DenseNet is useful in healthcare applications such as diagnosis [38], medical image [39], anatomical Brain segmentation [40], and surgical [40] as it is considerably more accurate with fewer parameters. This model's performance hinged mainly on its ability to offer better parameters and training efficiency through the reuse of features.…”
Section: B Densenet201mentioning
confidence: 99%